Evaluation of Equity in the Access to Drugs Financed by the Spanish National Health System through Royal Decree-Law 16/2012 concerning the Copayment Regime (Revista Iberoamericana de Bioética, 2023)
Equitable access to healthcare services constitutes one of the principles of the Spanish National Health System. Nevertheless, it has been shown that there is a percentage of citizens who suffer from financial hardship when paying for their prescriptions. This percentage fluctuates around 2.4% and affects certain people in vulnerable socioeconomic conditions, especially those who are polymedicated or who suffer chronic diseases. This article substantiates the right to access to prescription medication in equal conditions, and evaluates the data collected by state and non-governmental organizations that demonstrates inequality in access to medication. Pharmaceutical copayment can become an economic barrier for access to a patient’s prescribed drugs. The possible effects of the current copayment system remodeled by Royal Decree-Law 16/2012 and the different approaches for its improvement are analysed in light of the literature.
Keywords: equity; copayment; prescription drugs; Royal Decree-Law 16/2012; pharmaceutical poverty